Gaya Pemerintahan Sultan Abdul Hamid II pada Masa Turki Usmani - Kholifah, AtikaAuliaKholifah (Rihlah: Jurnal Sejarah dan Kebudayaan, 2022)
The history of the Ottoman Empire is one of the longest among other kingdoms. The Ottoman Empire was led by several Sultans, one of the most famous being Sultan Abdul Hamid II. His distinctive style of government and not wanting any interference from the West made him different from previous rulers. This study aims to examine more deeply the style of government of Sultan Abdul Hamid II, starting from the initial repeal, the efforts made, until the end of his reign by the Young Turk Movement. The research method used in this article is a qualitative method with literature study techniques. The results showed that the typical style of government of Sultan Hamid II was more or less influenced by his views on western nations who wanted to dominate the Ottoman Empire during the reign of his father and uncle. So that Sultan Abdul Hamid II has his own thoughts about government. Various efforts were made to maintain its power by facing various rebellions and improving education in an effort to prepare generations loyal to the kingdom. However, this effort actually became the trigger for the Turkish movement to overthrow his rule. Keywodrs: Government, Otoman Empite, Sultan Abdul Hamid II